Effects of a shock microcycle after COVID-19 lockdown period in elite soccer players - Vardakis, L.; Michailidis, Y.; Mandroukas, A.; Zelenitsas, C.; Mavrommatis, G. (Science & Sports, 2022)
Objectives Decreases in physical fitness are inevitable after two to six week period of detraining in athletes. Lockdown period changed the characteristics of soccer players` training. Aim of the study The aim of our study was to apply a HIIT shock-microcycle (SM) after return to training and assess its effect on players` performance. Equipment and methods Nineteen elite professional soccer players during the lockdown period (LP) from March to May 2020 (8 weeks) performed 3-4 individual training sessions per week. The training sessions included running boots of anaerobic short and aerobic prolonged duration intervals. Intensity was determined according to lab ergospirometry test 2 weeks before LP. All the players followed an indoor program, 3-6 sessions per week consisted of core, balance and flexibility exercises (~45 minutes). SM training content was same for both groups and took place the first two weeks after LP, consisted by eight high intensity interval training sessions (HIIT), two technique, two tactical sessions and two days off. Results Repeated sprint ability mean time (RSAMeanTime) and Repeated sprint ability performance-sprint no 4,5,6 (RSA4,5,6S) improved after SM (P = 0.025, Effect size: r2 = 0.331, P = 0.010, Effect size: r2 = 0.411, p = 0.009, Effect size: r2 = 0.418, P = 0.037, Effect size: r2 = 0.293, respectively. Yo-Yo intermitted recovery test level 2 (YYIR2TotalDistance) that covered by players during the 2nd measurement was 10.8% longer (P = 0.004, Effect size: r2 = 0.483). Also, the YYIR2HeartRateRecovery percentage was lower during the 2nd measurement (P = 0.014, Effect size: r2 = 0.107). Conclusions These results indicate that SM can improve YYIR2 and RSA performance thus it is a useful tool to regain physical attributes in a short period.